DIABETES IN PREGNANCY: CAUSES, CONSEQUENCES AND MODERN MANAGEMENT METHODS - Najmutdinova Dilbar Kamaritdinovna,; Rahmonova Umida Tohir kizi,; Abdumannonova Khidoyatxon Ganisher kizi, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article analyzes the causes of diabetes during pregnancy, its impact on maternal and fetal health, and modern diagnostic and management approaches. The study provides practical recommendations for detection, monitoring, and prevention of gestational diabetes in Uzbekistan. Hygienic, dietary, pharmacological, and psychological approaches are highlighted to ensure healthy development of mother and fetus.